2020
DOI: 10.1029/2020ja028251
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Ionosphere Observations in the Whole Atmosphere Community Climate Model with Thermosphere‐Ionosphere EXtension (WACCMX)

Abstract: A set of Observing System Simulation Experiments (OSSEs) are performed to assess the impact of assimilating Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) electron density profiles and ground-based Global Navigation Satellite System (GNSS) total electron content (TEC) observations in a whole atmosphere data assimilation system. The OSSEs are performed using the Whole Atmosphere Community Climate Model with thermosphere-ionosphere eXtension (WACCMX) with data assimilation provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…The second order divergence damping results in tidal amplitudes that are 50-100% too small. Pedatella et al (2020) demonstrated that the tidal amplitudes can be improved by using hourly data assimilation cycling; however, the present study makes use of existing simulations that utilized a six-hour data 265 assimilation cycle. The WACCMX+DART six-hourly analysis fields are combined with short-term (1-5 hour)…”
Section: Waccmx+dartmentioning
confidence: 99%
See 1 more Smart Citation
“…The second order divergence damping results in tidal amplitudes that are 50-100% too small. Pedatella et al (2020) demonstrated that the tidal amplitudes can be improved by using hourly data assimilation cycling; however, the present study makes use of existing simulations that utilized a six-hour data 265 assimilation cycle. The WACCMX+DART six-hourly analysis fields are combined with short-term (1-5 hour)…”
Section: Waccmx+dartmentioning
confidence: 99%
“…This is related to additional second order divergence damping that was included in the version of WACCMX+DART used for the present study, and has subsequently been removed, leading to increased tidal amplitudes in WACCMX+DART (Pedatella et al, 2020). As Fig.…”
mentioning
confidence: 99%
“…Pedatella et al. (2020) demonstrated that the problem of weak tidal amplitudes could largely be mitigated, though not entirely removed, by using an hourly data assimilation cycle. We thus evaluate the tides in WACCMX + DART with hourly data assimilation cycling during the 2009 SSW event.…”
Section: Model Observations and Analysis Methodsmentioning
confidence: 99%
“…(2012) suggested that day‐to‐day variability in DW1 might have been due to nonlinear interactions with the 6‐day planetary wave. The day‐to‐day variation of the atmospheric tidal amplitudes are also important for driving the day‐to‐day weather in the ionosphere (Kumar et al., 2014; Li et al., 2015; Liu, 2014; Miyoshi & Fujiwara, 2003; Pedatella et al., 2020). For example, during sudden stratospheric warming (SSW) events, the ionosphere/thermosphere shows large short‐term variability in response to lower atmosphere changes (Chau et al., 2012; Goncharenko et al., 2012; Goncharenko & Zhang, 2008; Oberheide et al., 2020).…”
Section: Introductionmentioning
confidence: 99%